Resistance profile of the most prevalent microorganisms in urine cultures at the Laboratório de Análises Clínicas Adolfo Lutz - Lobo Leite, Rodrigo; Marins Silva, Joelma; Maria Cardoso, Silvana; Rodrigues, Jefferson; Martins de Castro, Walessa; Lima de Oliveira Vargas, Laura; Almeida Silva de Lima, Beatriz (Seven Editora, 2023)
Urinary tract infection (UTI) is defined as microbial colonization and tissue invasion of some site of the genitourinary tract (GUT), capable of overcoming the defensive capacity of the host and causing injury. (Menin and Grazziotin, 2010). The main objective was to study the resistance profile of the most prevalent microorganisms in Urocultures at the Laboratory of Clinical Analysis Adolfo Lutz - FUNEC/CENTEC in order to have an overview of the resistance pattern of these microorganisms against the antibiotics used for the treatment of infections. During the study period, 316 urine cultures with antibiogram were performed in the clinical analysis laboratory Adolfo Lutz, FUNEC, UNIDADE CENTEC in Contagem/MG. Among these, 20.89% (66) presented a positive result, that is, microbial growth equal to or greater than 100,000 cfu/mL, with females being the most affected (83.34%). Escherichia coli was the microorganism with the highest incidence, followed by Staphylococcus aures and Klebsiela pneumoniae and in relation to the resistance profile of the isolated strains of Escherichia coli. A high level of resistance was observed for Ampicillin, Amoxicillin/Clavulinic Acid, Sulfametaxazole-Trimetropin, Nalidixic Acid, Cafazoline and Tetracycline respectively. DOI: 10.56238/pacfdnsv1-022